Analisis Prospek Dan Upaya Pengembangan Destinasi Wisata Pada Desa Maitara Kota Tidore Kepulauan Maluku Utara - Usman, Idham S.; Hasyim, Abdul Wahab; Sabuhari, Rahmat (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
The purposes of this research are 1) To find out the development of tourism potential on Maitara Island, Tidore City Islands; 2) To find out the prospects for the development of a tourist area on the island of Maitara, City of Tidore Islands. The sample in this study consisted of two types of samples, namely: regional samples and tourist samples. Percentage analysis was carried out using percentage calculations, the analytical techniques to be used were questionnaires, direct interviews, field observations, personal documents and official documents. The data is processed through a SWOT analysis. The results of the study show: that the Kailupa tourist attraction (one thousand money) is in the Quadrant I position, which means it still has a "good" situation. The Ake Bay tourist attraction is in the quadrant I position, which means it still has a "good" situation. Mangrove forest is in quadrant I position which means it still has a "good" situation with existing strengths able to take advantage of existing opportunities.